The impact of the Country’s health services’ expenditure on the success of MDGs, Goal 4/SDG 3: Reduction of child mortality in Uganda (2000-2016). - Nabukeera, Madinah (Archives of Business Research, 2020)
Safeguarding access to health services is a serious challenge for poor countries if the Sustainable Development Goals are to (SDGs) are to be achieved. This paper scrutinizes the case of Uganda, a country which is trying to improve its health sector amid a lot of challenges between 2000-2016 to assess how the country has performed in the reduction of child mortality given its expenditure. This study involved analyzing the available data drawn from various sources i.e., time series data on public health expenditure was obtained from Ministry of Health reports and the budget and Ministerial Policy Statements for the period 2000-2016. This data was further demarcated into parameters such as per capita government spending on health in Uganda shillings, health spending as a proportion of Gross Democratic Product (GDP) and private health spending as a proportion of total health spending. Findings revealed that non-significant negative effect of GDP per capita growth on infant mortality rate from 2000 to 2016, a negative effect of GDP per capita on under-five mortality in Uganda from 2000 to 2016, albeit the effect is non-significant (P>0.05), decline in Maternal Mortality Rate (MMR) from 527 death per 100,000 live birth in 1995 to 336 death per 100,000 live birth in 2016, and there is a negative but insignificant effect of health sector budget allocation on the MMR in Uganda since the P-value (0.199). Maternal mortality fell significantly in Uganda due to some interventions in the health sector. The decline is likely to have been cause due to supply and demand situations. There is need to improve funding in the health sector in order to improve quality health services through better coordination, health management, transportation, access, infrastructure at the district level.